Engineering mechanics : dynamics - Bedford, Anthony. (Addison-Wesley, 1996)
Introduction; Motion of a point; Force, mass and acceleration; Energy methods; Momentum methods; Planar kinematics of rigid bodies; Two-dimensional dynamics of rigid bodies; Energy and momentum in planar rigid-body dynamics; Three-dimensional kinematics and dynamics of rigid bodies; Vibrations.